Biosurfactant-producing and oil-degrading Bacillus subtilis strains enhance oil recovery in laboratory sand-pack columns - Gudina, Eduardo J.
Microbial Enhanced Oil Recovery (MEOR) technology uses microorganisms and their metabolites to retrieve unrecoverable oil from mature reservoirs. In situ stimulation of biosurfactant-producing and oil-degrading microorganisms reduces the capillary forces retaining the oil inside the reservoir and decreases its viscosity, thus promoting oil flow and consequently production. In this work, a sand-pack column model was designed to simulate oil recovery operations and evaluate mobilization of residual oil by the selected microorganisms. Four different hydrocarbon mixtures and three Bacillus subtilis strains isolated from crude oil samples were used. Additional oil recoveries ranged from 6 to 24% depending on the hydrocarbon mixture and microorganism used. Biosurfactant production was observed with all the microorganisms and hydrocarbon mixtures studied. The oils recovered after incubation with B. subtilis isolates showed a reduction in the percentage of long-chain n-alkanes and lower viscosity when compared with the original oils. The results obtained suggest that stimulation of the selected B. subtilis strains in situ can contribute to mobilize entrapped oil in mature reservoirs. (C) 2013 Elsevier B.V. All rights reserved.